OBSTACLES TO THE IMPLEMENTATION OF THE HIV/AIDS CURRICULUM IN GURUVE DISTRICT SECONDARY SCHOOLS IN ZIMBABWE - KASOWE, RITTAH (IJRDO- Journal of Educational Research, 2017)
The aim of this present study was to investigate constraints faced by secondary school teachers in the teaching and learning of HIV/AIDS education in Guruve District in Mashonaland Province of Zimbabwe. Specifically, it focused on HIV/AIDS content, evaluation of the subject, teacher qualifications, availability of resources, methodology as well as syllabus interpretation. The quantitative methodology was used and the descriptive survey design employed. The population consisted of all the 840 secondary school teachers in the district. Random sampling was used to select the 200 respondents. Data were collected using a questionnaire. The study revealed that teachers were finding it very difficult to discuss sex related issues with children. The study also revealed that teachers lacked the knowledge and confidence to teach HIV/AIDS education. The study recommends that teachers should be given proper training in the teaching of HIV/AIDS education. There is also need for teachers to be provided with relevant and adequate resources to effectively guide pupils on this subject.